The impact of mental health literacy on resource utilization for academic stress in a diverse student cohort - Nicole Sergeyev; Hannah Bodek; Anjali Krishnan; Laura Rabin; Katherine Fasano; Jaia Jones; Rona Miles (BMC Psychology)
Abstract Background Academic stress among some college students has intensified in the post-pandemic landscape. While stress management strategies for college students have been explored, it remains essential to investigate which resources students utilize to reduce academic stress and which are most helpful, particularly in diverse populations. Additionally, it is important to explore how mental health literacy (MHL), a contributing factor in the recognition of mental health issues and improving mental health outcomes, influences help-seeking behaviors, specifically for academic stress. Methods This study aims to help fill these knowledge gaps by exploring the relationships between academic stress, help-seeking behaviors, and MHL in a diverse sample of 450 undergraduate students (Mage = 21.47, 64.7% female, 76% non-white). Participants completed in-person assessments of a modified scale for academic stress and the Mental Health Literacy Assessment-college (MHLA-c) and reported their preferred academic stress reduction methods and demographics. Kruskal-Wallis tests were conducted to assess academic stress scores across demographic (gender, ethnicity) and academic (year in school, major) groups, while binary regression analyses were conducted to assess the predictive power of MHL in endorsing stress-reduction resources. Results Greater mental health knowledge significantly predicted using both informal (e.g., peer/family) and formal (e.g., counseling services) stress-reduction methods to alleviate academic stress. Hispanic and female students reported significantly higher levels of academic stress, primarily driven by concerns over assessments and pressure to meet personal expectations. Students predominately relied on social support and counseling services to reduce this stress and found peer and familial support the most helpful. Conclusions These findings are critical in shaping targeted intervention approaches to enhance MHL and in addressing the needs of high-risk groups to reduce academic stress burdens and consequences.